Exploration of Determinant Factors of Murabahah Microfinance Interest at BPRS Haji Miskin Pandai Sikek, West Sumatera - Syafiah, Zahratul; Gampito, Gampito; Andriany, Vicy (Surau Journal of Islamic Studies, 2025)
This study aims to analyze the factors influencing public interest in the murabahah microfinance product at BPRS Haji Miskin Pandai Sikek. Murabahah microfinance is one of the flagship products offering shariah-compliant financing solutions for micro-entrepreneurs in the West Sumatra region. The research employs a qualitative approach using in-depth interviews. The findings indicate that economic, social, and religious factors play significant roles in shaping the community's decision to access murabahah microfinance. Economic factors, such as the need for business capital and the speed of fund disbursement, are key reasons for choosing this product. Social factors, including religious influence and social networks, also contribute to the community's interest in this product. Furthermore, BPRS Haji Miskin actively enhances financial literacy through educational initiatives and community-based promotions, which effectively build trust and understanding about shariah principles and the benefits of murabahah products. This research contributes significantly to understanding the role of Islamic financial institutions in empowering local economies, particularly among micro-entrepreneurs in rural areas.